Longitudinal imaging of reading and naming recovery after stroke. Issue 7 (3rd July 2018) - Long, Charltien; Sebastian, Rajani; Faria, Andreia V.; Hillis, Argye E.
ABSTRACT: Background : Functional neuroimaging techniques can provide a unique window into the neural basis of language recovery after a stroke. The functional neuroimaging literature on post-stroke language recovery is complex; multiple factors such as the time post-stroke, degree of initial impairment, nature of the task, and lesion location and size influence recovery patterns. Some of these factors may not be applicable across different stroke participants, and therefore, influence recovery trajectories in vastly different manners across patients. Aims : The aim of this paper is to examine longitudinal changes in brain activation patterns of reading and naming recovery in participants with posterior cerebral artery (PCA) strokes with varying degrees of initial language impairment. Methods & Procedures : Five participants with PCA strokes and five healthy controls underwent language testing and functional MRI with a covert reading task and an overt picture-naming task. Stroke participants underwent language testing and scanning at the three time points: 2–5 weeks (T1, subacute phase), 4–7 months (T2, chronic phase), and 11–13 months (T3, chronic phase). Healthy controls underwent language testing and fMRI once. Outcomes & Results : Language testing indicated that there were varying degrees of reading and naming recovery or decline from the subacute to the chronic phase. With regard to task-based fMRI, we found that for most participants, naming consistently activated a diffuse bilateral network of frontal, temporal, parietal, and occipital regions across the three time points. In contrast, for the reading task, functional activation across the three time points was more left lateralized with a right to left shift in peak activation from the subacute to the chronic phase. Conclusions : These results indicate that the patterns of activation during language processing is highly dependent on the task and phase of recovery, and these results may have implications for neurally targeted non-invasive brain stimulation techniques.